On three-dimensional ALE finite element model for simulating deformed interstitial medium in the presence of a moving needle. (15th December 2016) - Deleuze, Yannick; Thiriet, Marc; Sheu, Tony W.H.
Highlights: Brinkman equations to describe the flow through a deformed porous medium. Three-dimensional ALE finite element model. Describe the physical stress affecting cells during acupuncture treatment. Abstract: The effect of inserted needle on the subcutaneous interstitial flow is studied. Our goal is to describe the physical stress affecting cells during acupuncture needling. The convective Brinkman equations are considered to describe the flow through a fibrous medium. Three-dimensional simulations are carried out by employing an ALE finite element model. Numerical studies illustrate the acute physical stress developed by the implantation of a needle.